2008
DOI: 10.1146/annurev.arplant.59.032607.092830
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Nitric Oxide Signaling in Plants

Abstract: A decade-long investigation of nitric oxide (NO) functions in plants has led to its characterization as a biological mediator involved in key physiological processes. Despite the wealth of information gathered from the analysis of its functions, until recently little was known about the mechanisms by which NO exerts its effects. In the past few years, part of the gap has been bridged. NO modulates the activity of proteins through nitrosylation and probably tyrosine nitration. Furthermore, NO can act as a Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
459
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 719 publications
(480 citation statements)
references
References 96 publications
8
459
0
13
Order By: Relevance
“…NO is also found to act as a regulatory factor for embryonic dormancy break in apple by stimulating biosynthesis of ethylene (Gniazdowska et al 2007). It has been reported that NO can function as an endogenous mediator in diverse plant physiological processes but its production, effect and associated mechanisms are not known very precisely (Besson-Bard et al 2008). Likewise, Wills et al (2000) and Leshem et al (2000), Eum et al (2009) also reported that NO affects the ethylene production through its direct regulatory effect on the enzymes of ethylene biosynthesis (ACC-synthase and ACC-oxidase) and also on their genes during ripening of tomato.…”
Section: Water Vapours/water Status In Fruitmentioning
confidence: 99%
“…NO is also found to act as a regulatory factor for embryonic dormancy break in apple by stimulating biosynthesis of ethylene (Gniazdowska et al 2007). It has been reported that NO can function as an endogenous mediator in diverse plant physiological processes but its production, effect and associated mechanisms are not known very precisely (Besson-Bard et al 2008). Likewise, Wills et al (2000) and Leshem et al (2000), Eum et al (2009) also reported that NO affects the ethylene production through its direct regulatory effect on the enzymes of ethylene biosynthesis (ACC-synthase and ACC-oxidase) and also on their genes during ripening of tomato.…”
Section: Water Vapours/water Status In Fruitmentioning
confidence: 99%
“…1). NO was shown to interact with Hb from different plant species in a Hb/NO cycle, in which the excess NAD(P)H is oxidized for the conversion of NO into nitrate (Hebelstrup et al 2012;Besson-Bard et al 2008b). When alfalfa plants overexpressing Hb were compared to wild type or to Hb-antisense plants, symptoms of hypoxia were improved, leading to a longer survival of the Hb overexpressors (Dordas et al 2003a).…”
Section: Nitrite Reduction and Nitric Oxide Productionmentioning
confidence: 99%
“…Ce constat est à l'origine de controverses quant à l'existence même d'une protéine à activité NOS chez les plantes supé-rieures [8,9]. Signalons que d'autres voies de synthèse de NO, enzymatiques ou non, et utilisant des polyamines ou le nitrite comme substrats, ont également été rapportées [3,4]. Pour l'essentiel, ces voies restent énigmatiques.…”
Section: Synthèse De No Chez Les Plantesunclassified
“…Ces travaux, de même que les nombreuses études publiées ultérieurement, ont démontré que la reconnaissance de l'agent pathogène déclenche une production rapide de NO simultanée à celle des formes actives de l'oxygène [17,18]. Selon le modèle d'étude, le NO est produit en premier lieu dans les chloroplastes, le noyau ou le cytosol, puis diffuse rapidement dans le milieu extracellulaire et peut être détecté dans l'atmosphère environnant la plante infectée [4]. La nitrate réductase, de même que des activités catalysées par des NOS potentielles, ont été associées à cette synthèse mais très peu de données sont disponibles quant à leur régulation.…”
Section: Synthèse De No Chez Les Plantesunclassified
See 1 more Smart Citation